2022
DOI: 10.1177/00033197221134757
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Cardiovascular Diseases in Saliva and Gingival Crevicular Fluid: A Review

Abstract: Due to the fact that cardiovascular diseases (CVDs) have become the most serious problem in public health, there is a need for new and efficient methods for screening and early detection. In the recent literature, saliva and gingival crevicular fluid (GCF) have been gaining recognition as sources of many potential biomarkers of various systemic diseases, mainly because of correlation between the level of some compounds in the blood and saliva and association between the composition of saliva and health status.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
(193 reference statements)
0
1
0
Order By: Relevance
“…It was found that periodontitis was a significant predictor of GCF miRNAs associated with CVD risk [ 27 ]. Furthermore, fluid from gingival pockets was examined as material for the evaluation of biomarkers in cardiovascular disorders such as atherosclerosis, arterial hypertension, coronary heart disease, or ischemic stroke [ 28 ]. In the pediatric population, researchers also utilized GCF as a means of identifying interleukin-1α (IL-1α) as a novel non-invasive marker for the detection of external inflammatory root resorption, which can occur following dental trauma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that periodontitis was a significant predictor of GCF miRNAs associated with CVD risk [ 27 ]. Furthermore, fluid from gingival pockets was examined as material for the evaluation of biomarkers in cardiovascular disorders such as atherosclerosis, arterial hypertension, coronary heart disease, or ischemic stroke [ 28 ]. In the pediatric population, researchers also utilized GCF as a means of identifying interleukin-1α (IL-1α) as a novel non-invasive marker for the detection of external inflammatory root resorption, which can occur following dental trauma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%